Guías para el uso de la secuencia didáctica y metodologías ctivas de enseñanzas y aprendizaje para el desarrollo de competencias de lectura y escritura - Ferrer Mendoza, Yicera (Corporación Universitaria Americana, 2023)
It is evident that having solid reading and writing skills is fundamental to achieve an outstanding academic performance during the university stage; both competencies constitute modes of knowledge construction and, therefore, are fundamental in the social, academic and professional development of human beings. In this sense, reading and writing skills allow students to integrate into the disciplinary discursive communities and to achieve participation and success in the tasks of textual analysis and production, necessary for their learning process (Carlino, 2005). Thus, several researches have been concerned with investigating the deficiencies in the reading and writing levels of students entering university (Colectivo Comunicación, 2002; Flórez et al., 2005; Pérez and Rincón, 2013), since this difficulty is related to academic failure and dropout in higher education (Benítez et al., 2021; Guerrero, 2018; Mendoza et al., 2022; Olave-Arias et al., 2013).